Delayed tension gastrothorax caused necrosis of stomach and re-expansion pulmonary edema: a case report - Yuki Mochida; Ryohei Nishizawa; Koji Ochiai; Yoshitaka Inoue; Yasuhiko Kaita; Yoshihiro Yamaguchi (Surgical Case Reports)
Abstract Background Traumatic tension gastrothorax is a rare and potentially fatal condition occurring in patients with congenital or acquired diaphragmatic defects. Traumatic tension gastrothorax leads to acute and severe respiratory distress. Delayed tension gastrothorax that develops late during injury can be more severe. Case presentation An 84-year-old woman was brought to our facility with cardiac arrest and returned to spontaneous circulation after 2 min of cardiopulmonary resuscitation. Computed tomography showed diaphragmatic injury and tension gastrothorax due to trauma because of a fall episode few days earlier. Emergency thoracotomy and laparotomy was performed, because nasogastric tube insertion failed. There was a partially necrotic stomach in the chest cavity. The stomach was retracted from the thoracic cavity into the abdominal cavity and placed in its proper position. There was a 5 cm tear of the diaphragm. The tear was sutured and closed and then the necrotic area of the stomach was resected. Although the surgery relieved the intrathoracic compression, it resulted in re-expansion pulmonary edema immediately after surgery and hypoxemia. The patient was unable to overcome the hypoxemic state and eventually died. Conclusions Delayed tension gastrothorax can lead not only to obstructive shock due to intrathoracic compression but also to more severe organ ischemia and re-expansion pulmonary edema due to insufflation.